Approach Matters: The Kinetics of Interfacial Inverse‐Electron Demand Diels–Alder Reactions. Issue 53 (23rd August 2017) - Sen, Rickdeb; Gahtory, Digvijay; Escorihuela, Jorge; Firet, Judith; Pujari, Sidharam P.; Zuilhof, Han
Abstract: Rapid and quantitative click functionalization of surfaces remains an interesting challenge in surface chemistry. In this regard, inverse electron demand Diels–Alder (IEDDA) reactions represent a promising metal‐free candidate. Herein, we reveal quantitative surface functionalization within 15 min. Furthermore, we report the comprehensive effects of substrate stereochemistry, surrounding microenvironment and substrate order on the reaction kinetics as obtained by surface‐bound mass spectrometry (DART‐HRMS). Abstract : Nailing the landing : For click reactions on a surface, the angle of approach matters greatly. We show for closely monitored inverse electron demand Diels–Alder reactions that fast and quantitative landings are feasible.